Alternative currency as the common good (Economic and Political Thought, 2014)
Alternative currencies also known as local currencies are becomingmore and more popular means of payment. Across the world, there arecurrently about four thousand alternative currencies. They are not issued bystates, but by counties, cities and even by persons. A dynamic growth of theInternet and technological and communication innovations contributes to thedevelopment of digital alternative currencies due to a possibility of creatingplatforms, exchange webpages and the establishment of on-line communities.The subject of the article is an analysis of an alternative currency as thecommon good on the basis of literature research. To that end, the term of‘common’ is explained. Next, the term ‘alternative currency’ and examples ofsuch currencies are presented.